Temporal modeling of head movement during facial expression via dual pivot tracking system: a case of disgust - Yusoff, Fakhrul Hazman; Wirza O.K.Rahmat, Rahmita; Sulaiman, M.Nasir; Shaharom, Mohamed Hatta; Abdul Majid, Hariyati Shahrima (IMECS, 2009)
Temporal modeling od facial expression is very important in various fields which include expression recognition, realism in computer animation and behavioral study in psychological field. While various researches are currently being done to capture the movement of facial features for its temporal property, not much is being said about the head movement during the facial expression process. The absence of head movement description can lead to incomplete expression description especially in the case of disgust where head movement can be a vital element for its depiction. Therefore, this paper proposes a method to track the movement of the head by using a dual pivot head tracking system (DPHT). In proving its usefulness, the tracking system will then be applied to track the movement of subjects depicting disgust. A simple statistical two-tailed analysis and visual rendering comparison will be made with a system that uses only a single pivot to illustrate the practicality of using DPHT. Results show that better depictions of expression can be implementad if the movement of the head is incorporated.